Positive plate, preparation method thereof and lithium ion battery

By combining Ti3C2 film material on the surface of the positive electrode sheet of the lithium-ion battery, the shortcomings of lithium-ion battery in terms of safety and energy density are solved, and high safety and energy density are achieved. The battery is verified through needle puncture experiments. Safety performance.

CN119208523APending Publication Date: 2024-12-27中汽新能(天津)电池科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411284563.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have shortcomings in taking into account safety and energy density, especially in terms of thermal stability and safety performance of high-nickel ternary materials.

Method used

Using the Ti3C2 film material composited with heat transfer roll press on the surface of the active material layer, a two-dimensional nanoflake Ti3C2 film with low ion diffusion resistance and high storage capacity was prepared by intercalating and peeling the two-dimensional nano-chip Ti3C2 powder, and Combine it onto the positive electrode.

Benefits of technology

It achieves a balance between high safety and high energy density, improves the thermal stability and rate performance of the battery, simplifies the process flow, reduces costs, and verifies the safety performance of the battery through needle puncture experiments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208523A_ABST
    Figure CN119208523A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a positive plate, a preparation method thereof and a lithium ion battery, and the positive plate comprises a current collector, an active substance layer arranged on one side or two sides of the current collector, and a Ti3C2 film material arranged on the surface of the active substance layer. According to the technical scheme, the Ti3C2 thin film material is compounded on the surface of the active substance layer, the battery with high safety and high energy density can be achieved, the method is simple in operation, low in industrialization implementation difficulty and low in cost, and in addition, the Ti3C2 thin film material is high in surface porosity and suitable for lithium ion diffusion and electrolyte isolation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a positive electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Environmental protection and energy consumption are two major problems that humans currently need to solve. With the increase in resource consumption, environmental pollution is becoming more and more serious, and the ecological environment is being damaged. In order to improve the living environment of mankind, we need to find a green and clean energy to improve the current situation.

[0003] For new, green, energy storage devices, while being concerned about their greenness, high power density and high energy density are important indicators of whether they can truly replace traditional energy storage and transportation systems. New power systems, especially secondary batteries or supercapacitors, are currently important green energy storage devices, and the key technical part is energy storage materials with good performance.

[0004] MXene is a transition metal carbide or nitride with a two-dimensional layered structure similar to graphene that was discovered in recent years. There are nearly 70 types of MXene discovered so far, including Ti3C2, Ti2C, V2C, Nb2C, Nb4C3, Ta4C3, Ti4N3, etc. Due to its good conductivity, large specific surface area and high strength, MXene has broad application prospects in energy storage, electronics, composite materials, sensors and other fields.

[0005] At present, lithium-ion battery products have been widely used in power batteries, consumer products, and energy storage fields, but how to balance the safety and energy density of batteries? Safety is the application basis of lithium-ion batteries and the guarantee for people to use electronic products. However, people have higher and higher requirements for battery life. The positive electrode material needs to use high-nickel ternary materials. How to ensure the thermal stability of the material? The ternary materials are modified by doping, coating and other methods to improve the stability of the material. Yuan et al. prepared LiNi by coprecipitation method. 0.8 Mn 0.1 Co 0.1 O2 materials, and studied the effects of doping with three elements, Li, Mg, and Al, on the material properties. 0.8 Mn 0.1 Co 0.1 The lattice constant of O2 material decreases, I (003) / I (104) The cation mixing degree is reduced, and the stability of the layered structure is improved; Xiong et al. prepared LiF in-situ coated LiNi 0.8 Mn 0.1 Co 0.1O2 materials. Chen et al. used a hydrothermal method to coat nano-TiO2 on LiNi 0.6 Co 0.2 Mn 0.2 On the surface of O2 cathode material, Woo et al. prepared SO4 2– / ZrO2 mixed coated LiNi 0.8 Mn 0.1 Co 0.1 O2 positive electrode materials have effectively improved the stability and electrochemical reversibility of the materials. However, the above methods use material modification, but the improvement of battery safety performance is limited. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a positive electrode sheet and a preparation method thereof and a lithium ion battery.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A positive electrode sheet comprises a current collector, an active material layer arranged on one side or both sides of the current collector, and a Ti3C2 thin film material arranged on the surface of the active material layer.

[0009] The thickness of the Ti3C2 thin film material is 5-50 μm, preferably 5-30 μm, and more preferably 20 μm.

[0010] The preparation method of the Ti3C2 thin film material comprises the following steps: 1) adding an intercalating agent to two-dimensional nano Ti3C2 powder to obtain Ti3C2MXene; 2) dissolving Ti3C2MXene in water to obtain a colloidal aqueous solution; 3) filtering the colloidal aqueous solution using a cellulose microporous filter membrane and then drying at low temperature to obtain two-dimensional nano Ti3C2 films of different thicknesses.

[0011] The intercalant in step 1) is one or a mixture of ferric chloride, ammonium nitrate, ammonium carbonate, ammonium bicarbonate, sodium carbonate, or ferric carbonate.

[0012] The specific steps of step 1) are: dissolving two-dimensional nano Ti3C2 powder in water, adding an intercalation agent and mixing, stirring for 1-4 hours, filtering the mixed solution, and drying at 40-60 degrees to obtain intercalated Ti3C2MXene;

[0013] Preferably, the molar ratio of the two-dimensional nano-Ti3C2 powder to the intercalation agent is (0.5-2):1; preferably 1:1;

[0014] Preferably, the mass volume ratio of the two-dimensional nano Ti3C2 powder to water is 1: (50-200) g / mL; preferably 1: 100 g / mL.

[0015] The two-dimensional nano Ti3C2 powder is prepared in the following manner: the block Ti3AlC2 is crushed and sieved to obtain a Ti3AlC2 raw material powder with a particle size of less than 80um; the Ti3AlC2 raw material powder and HF aqueous solution are placed in a closed container and stirred; after the reaction is completed, the two-dimensional nano Ti3C2 powder is filtered, washed, and dried; preferably, the mass concentration of the HF aqueous solution is 10-40%; preferably 10%.

[0016] Preferably, the pore size of the cellulose microporous filter membrane is 100 nm and the filter membrane diameter is 25 mm.

[0017] The preparation method of the positive electrode sheet comprises the following steps: applying the positive electrode coating to the surface of the positive electrode collector, rolling and drying to obtain a ternary electrode sheet; compounding the Ti3C2 thin film material on the surface of the ternary electrode sheet to obtain the positive electrode sheet; preferably, a thermal transfer thin film composite roller machine is used to compound the Ti3C2 thin film material on the surface of the ternary electrode sheet.

[0018] Preferably, the thickness of the ternary electrode piece is 100-200 μm, preferably 160 μm.

[0019] The positive electrode coating comprises a positive electrode active material, a positive electrode conductive agent and a positive electrode binder;

[0020] Preferably, the positive electrode active material is a ternary material NCM;

[0021] Preferably, the positive electrode conductive agent is a mixture of CNT and SP;

[0022] Preferably, the positive electrode binder is PVDF; the molecular weight of the PVDF is 100,000-300,000;

[0023] Preferably, the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is 95:2:3.

[0024] The present invention also includes a lithium ion battery, comprising the positive electrode sheet, the negative electrode sheet and the diaphragm.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The technical solution of the present application can achieve both high safety and high energy density batteries by thermally transferring and rolling the composite Ti3C2 thin film material on the surface of the active material layer. The method is simple to operate, has low difficulty in industrialization, and is low in cost. In addition, the surface porosity of the Ti3C2 thin film material is high, which is suitable for lithium ion diffusion and isolation of electrolyte. Among them, the Ti3C2 thin film material is obtained by a new preparation method, specifically a two-dimensional nano-sheet Ti3C2 made from Ti3AlC2. The obtained two-dimensional nano-sheet Ti3C2 is intercalated and peeled by a new intercalation agent, and the interlayer spacing becomes larger. The material has low ion diffusion resistance, low open circuit voltage and high storage capacity. Two-dimensional nano-sheet Ti3C2 thin film materials of different thicknesses have high specific surface area, good conductivity and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 XRD patterns of Ti3AlC2, Ti3C2 and Ti3C2MXene;

[0028] Figure 2 a is the SEM image of Ti3C2, b is the SEM image of Ti3C2MXene, and c is the TEM image of Ti3C2 thin film material;

[0029] Figure 3 Schematic diagram of the composite structure of the positive electrode sheet;

[0030] Figure 4 This is the DSC comparison diagram of the positive electrode at different voltages;

[0031] Figure 5 The safety performance test results of the positive electrode battery of Example 1 and the comparative example are shown;

[0032] Figure 6 It is a comparison chart of the rate performance of the battery of Example 1 and the comparative example.

[0033] Figure 7 The safety performance test results of the positive electrode battery of Example 2 and the comparative example are shown; DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0035] Example

[0036] 1. Ti3C2 thin film material is prepared by the following method:

[0037] 1) Two-dimensional nano-Ti3C2 powder is added with an intercalation agent to obtain Ti3C2MXene;

[0038] 1.1) First, prepare two-dimensional nano Ti3C2 powder: crush the bulk MAX phase Ti3AlC2, sieve it, and obtain Ti3AlC2 raw material powder with a particle size of less than 80um; quantitatively weigh 1g of Ti3AlC2, dissolve it in 10% HF, and react it for 8-12h under stirring; after the reaction, filter the reaction solution, wash the solid with a large amount of water, and then dry it at 40-60°C to obtain two-dimensional nano-sheet Ti3C2 powder;

[0039] 1.2) Then, the two-dimensional nano Ti3C2 powder is intercalated and exfoliated, comprising the following steps: quantitatively weighing 1 g of two-dimensional nano-sheet Ti3C2 powder, dissolving it in 100 ml of water, and mixing the intercalation agent ferric chloride with the two-dimensional nano-sheet Ti3C2 powder in a molar ratio of 1:1, and stirring the solution for 1-4 hours; filtering the mixed solution, and drying it at 40-60°C for 24 hours to obtain intercalated two-dimensional nano-sheet Ti3C2 powder Ti3C2Mxene.

[0040] 2) Ti3C2MXene is dissolved in water to obtain a colloidal aqueous solution; after 1g of Ti3C2MXene is dissolved in 100ml of water, the solution is ultrasonicated at 100W for 30-60min to obtain a colloidal aqueous solution with a mass fraction of 1%;

[0041] 3) After the colloidal aqueous solution is filtered through a cellulose microporous filter membrane, it is dried at low temperature to obtain two-dimensional nano-Ti3C2 films of different thicknesses. Take 10ml-100ml of Ti3C2 intercalation solution, filter it through a cellulose microporous filter membrane, the pore size of the filter membrane is 100nm, the filter membrane diameter is 25mm, and dry it at 40-60℃ for 24h to obtain two-dimensional nano-sheet Ti3C2 films with thicknesses of 5, 20, and 50μm.

[0042] As attached Figure 1 XRD patterns of Ti3AlC2, Ti3C2 (intercalated Ti3C2) and Ti3C2MXene (Ti3C2 after exfoliation). During the exfoliation process, Al is selectively removed to obtain two-dimensional Ti3C2. Figure 1 The (002) peak of the Ti3C2 nanostructured carbon ... After exfoliation and insertion, the (002) peak further shifted to 2θ=7.0°, and c increased to 25.3, and the exfoliated and intercalated Ti3C2MXene was obtained.

[0043] 2. The positive electrode is prepared in the following manner:

[0044] The positive electrode coating is applied to the surface of the positive electrode current collector, and the ternary electrode sheet is obtained after rolling and drying; the Ti3C2 thin film material is compounded on the surface of the ternary electrode sheet to obtain the positive electrode sheet; preferably, the Ti3C2 thin film material is compounded on the surface of the ternary electrode sheet by a thermal transfer thin film composite roller machine; Figure 3 A positive electrode sheet is shown, comprising a current collector 1, an active material layer 2 arranged on one side or both sides of the current collector, and a Ti3C2 thin film material 3 arranged on the surface of the active material layer.

[0045] Specifically, the following steps are included: the positive electrode active material ternary material NCM (nickel cobalt manganese oxide, nickel content greater than or equal to 90%), the positive electrode conductive agent (a mixture of CNT and SP) and the positive electrode binder PVDF are mixed in a mass ratio of 95:2:3 and then homogenized; the slurry solvent is NMP, the slurry viscosity is controlled to be less than 12000CP, the solid content is controlled to be more than 67%, and the coating amount is 600g / m 2 , and obtain the ternary electrode;

[0046] The Ti3C2 thin film material and the ternary electrode sheet obtained above are passed through a thermal transfer thin film composite roller machine, with the ternary electrode sheet on the lower layer and the two-dimensional nano-sheet Ti3C2 thin film on the upper layer. By heating at 130°C and maintaining it for 5 minutes, pole sheets composited with two-dimensional nano-sheet Ti3C2 and ternary materials of different thicknesses are obtained. The thickness of the two-dimensional sheet Ti3C2 film is 5μm, 20μm, and 50μm, and the thickness of the positive electrode active material coating is 160μm, and the positive electrode sheet is made.

[0047] The molecular weight of the PVDF is 100,000-300,000; the PVDF with this molecular weight can be partially melted below 130°C, and the two-dimensional nano-sheet Ti3C2 film can be bonded together by using thermal transfer technology.

[0048] 3. Preparation of lithium-ion batteries:

[0049] The positive electrode sheet of step 2 is used, the negative electrode sheet is made of silicon-carbon and graphite composite material, the charging capacity is 800mAh / g, and then a conventional (12+4)μm PE ceramic diaphragm is used to make a laminated soft-pack battery, and the electrolyte is a conventional ternary liquid electrolyte to make a composite battery model SP14103310 soft-pack battery. A conventional positive electrode sheet, that is, a positive electrode sheet that does not contain a two-dimensional nano-sheet crystal Ti3C2 film, is used as a comparative example for testing.

[0050] The battery with a positive electrode of 5μm two-dimensional nanosheet Ti3C2 thin film material (composite solution 1) weighs 843g, 0.2C standard capacity, voltage range of 2.5V-4.3V, capacity of 89.1Ah, and energy density of 369.9wh / kg. The battery of the benchmark solution (comparative example) weighs 835g, 0.2C standard capacity, voltage range of 2.5V-4.3V, capacity of 89Ah, and energy density of 372wh / kg. Compared with the composite solution, the energy density of the benchmark solution is basically the same.

[0051] like Figure 4 As shown, the positive electrode uses 5μm two-dimensional nano-sheet Ti3C2 thin film material. The battery of this scheme is charged to 4.4V, 4.45V, and 4.5V, and then the three types of battery positive electrodes are disassembled for DSC testing. Compared with the comparative example, the maximum combustion temperature of the composite scheme at 4.5V is 226.5℃, which is 12.1℃ higher than the combustion temperature of the benchmark scheme (comparative example) at 4.3V. However, the calorific value of the composite scheme at 4.5V is 45.1J / g, which is 51% lower than the benchmark scheme at 4.3V. From the intrinsic point of view of the electrode, the thermal stability of the composite material is better than that of the low-voltage benchmark scheme at higher voltage, indicating that the use of two-dimensional nano-sheet Ti3C2 thin film composite ternary material can greatly improve the safety performance of its electrode.

[0052] like Figure 5 As shown, when the batteries of the baseline solution and the composite solution are charged to 4.3V, the batteries are subjected to a rigorous slow puncture test. The experimental conditions are a 5mm steel needle at a speed of 80mm / s. The battery is punctured and maintained for 1 hour. The battery is required not to catch fire or explode. After comparison after testing, compared with the control example, the battery temperature of the baseline solution exceeds 300°C, and the battery catches fire and burns. However, the battery of the composite solution does not catch fire or explode. The maximum temperature of the battery after puncture is only 41°C, and it can pass the puncture test. The battery energy density is above 369wh / kg, which solves the safety problem of the battery under high energy density.

[0053] like Figure 6 As shown, the rate discharge performance of the benchmark and composite scheme batteries was tested. The batteries were tested at 25°C, and after being fully charged at 0.2C, they were discharged at different rates. Compared with the control example, in terms of the battery capacity retention rate at 1C discharge, the benchmark and composite schemes were not much different, but in terms of 2C, 3C, 4C, and 5C battery discharge, the rate performance of the composite scheme battery has great advantages, especially at 5C rate discharge, the capacity retention rate of the composite scheme is 96.1%, the capacity retention rate of the benchmark scheme is 89.4%, and the discharge capacity is increased by 6.7%, indicating that the composite scheme battery has obvious advantages in high-rate batteries and is suitable for high-rate discharge batteries.

[0054] The battery with a positive electrode of 20μm two-dimensional nano-sheet Ti3C2 thin film material (composite solution 2) weighs 875g. As the film thickens, the battery weight increases slightly. The battery voltage range is 2.5-4.5V, the capacity is 92.5Ah, and the energy density is 378.46Wh / kg. The battery voltage platform is improved, the capacity is improved, and the battery energy density is improved. Figure 7 As shown, the battery safety test comparison found that when the battery charging voltage was increased to 4.5V, the battery safety performance of the composite 20μm two-dimensional nanosheet Ti3C2 thin film material could pass the needle puncture test.

[0055] The battery with a positive electrode made of 50μm two-dimensional nanosheet Ti3C2 thin film material (composite solution 3) weighs 915g. As the film thickens, the battery weight increases significantly. The voltage range is 2.5-4.35V, the capacity is 88Ah, and the energy density is 336.6Wh / kg. The reason for the low energy density is that on the one hand, the increase in the thickness of the Ti3C2 thin film material significantly increases the weight of the battery. On the other hand, the increase in the thickness of the Ti3C2 thin film material increases the lithium ion transmission distance, thereby increasing the polarization of the battery, resulting in a decrease in the battery voltage platform. These two reasons significantly reduce the battery energy density and significantly improve the battery safety performance.

[0056] Research shows that the battery capacity retention rate of the positive electrode obtained by compounding 5μm-30μm two-dimensional nano-sheet Ti3C2 thin film material with a ternary electrode can be improved, and the safety performance is significantly improved. In particular, the battery obtained by compounding 20μm two-dimensional nano-sheet Ti3C2 thin film material with a ternary electrode can pass the 4.5V puncture test.

[0057] In summary, the technical solution of the present application can achieve both high safety and high energy density batteries by heat transfer roller pressing of composite Ti3C2 thin film material on the surface of the active material layer. The method is simple to operate, has low difficulty in industrialization and low cost. In addition, the surface porosity of the Ti3C2 thin film material is high, which is suitable for lithium ion diffusion and isolation of the electrolyte.

[0058] Among them, Ti3C2 thin film materials are obtained by a new preparation method. The two-dimensional nano-sheet Ti3C2 made by Ti3AlC2 is intercalated and peeled by a new intercalation agent, and the interlayer spacing becomes larger. The material has low ion diffusion resistance, low open circuit voltage and high storage capacity. Two-dimensional nano-sheet Ti3C2 thin film materials with different thicknesses have high specific surface area, good conductivity and rate performance.

[0059] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A positive electrode sheet, characterized in that: It comprises a current collector, an active material layer arranged on one side or both sides of the current collector, and a Ti3C2 thin film material arranged on the surface of the active material layer.

2. The positive electrode sheet according to claim 1, characterized in that: The thickness of the Ti3C2 thin film material is 5-50 μm, preferably 5-30 μm, and more preferably 20 μm.

3. The positive electrode sheet according to claim 1, characterized in that: The Ti3C2 thin film material is prepared by the following method: 1) adding an intercalating agent to two-dimensional nano Ti3C2 powder to obtain Ti3C2MXene; 2) dissolving Ti3C2MXene in water to obtain a colloidal aqueous solution; 3) filtering the colloidal aqueous solution using a cellulose microporous filter membrane and then drying at low temperature to obtain two-dimensional nano Ti3C2 films of different thicknesses.

4. The positive electrode sheet according to claim 3, characterized in that: The intercalant in step 1) is one or a mixture of ferric chloride, ammonium nitrate, ammonium carbonate, ammonium bicarbonate, sodium carbonate, or ferric carbonate.

5. The positive electrode sheet according to claim 3, characterized in that: The specific steps of step 1) are: dissolving two-dimensional nano Ti3C2 powder in water, adding an intercalation agent and mixing, stirring for 1-4 hours, filtering the mixed solution, and drying at 40-60 degrees to obtain intercalated Ti3C2MXene; Preferably, the molar ratio of the two-dimensional nano-Ti3C2 powder to the intercalation agent is (0.5-2):1; preferably 1:1; Preferably, the mass volume ratio of the two-dimensional nano Ti3C2 powder to water is 1: (50-200) g / mL; preferably 1: 100 g / mL.

6. The positive electrode sheet according to claim 3, characterized in that: The two-dimensional nano Ti3C2 powder is prepared in the following manner: the block Ti3AlC2 is crushed and sieved to obtain a Ti3AlC2 raw material powder with a particle size of less than 80um; the Ti3AlC2 raw material powder and HF aqueous solution are placed in a closed container and stirred; after the reaction is completed, the two-dimensional nano Ti3C2 powder is filtered, washed, and dried; preferably, the mass concentration of the HF aqueous solution is 10-40%; preferably 10%.

7. The positive electrode sheet according to claim 3, characterized in that The pore size of the cellulose microporous filter membrane is 100 nm, and the filter membrane diameter is 25 mm.

8. A method for preparing a positive electrode sheet according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: applying the positive electrode coating to the surface of the positive electrode current collector, rolling and drying to obtain a ternary electrode sheet; compounding the Ti3C2 thin film material on the surface of the ternary electrode sheet to obtain the positive electrode sheet; preferably, a thermal transfer thin film compounding roller machine is used to compound the Ti3C2 thin film material on the surface of the ternary electrode sheet; Preferably, the thickness of the ternary electrode piece is 100-200 μm, preferably 160 μm.

9. The method for preparing a positive electrode sheet according to claim 7, characterized in that: The positive electrode coating comprises a positive electrode active material, a positive electrode conductive agent and a positive electrode binder; Preferably, the positive electrode active material is a ternary material NCM; Preferably, the positive electrode conductive agent is a mixture of CNT and SP; Preferably, the positive electrode binder is PVDF; the molecular weight of the PVDF is 100,000-300,000; Preferably, the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is 95:2:

3.

10. A lithium ion battery, characterized in that: It comprises the positive electrode sheet, the negative electrode sheet and the separator as described in any one of claims 1 to 9.